Note:
Your first question is missing the y-intercept, so I am solving the 2nd question, but the procedure to solve each of the questions is the same.
Answer:
The equation in the standard form is:
![(2)/(3)x\:+\:y\:=-4](https://img.qammunity.org/2022/formulas/mathematics/college/hl68bc7lmmnqzc970548xfdjbac9c2y0x8.png)
Explanation:
Given
Slope m = -2/3
y-intercept = -4
We know that the slope-intercept form of the line equation
y = mx+b
where
now substituting m = -2/3 and y-intercept b = -4 in the slope-intercept of the line equation
![y = mx+b](https://img.qammunity.org/2022/formulas/mathematics/college/cg45g3nq46tuir13g5pg3kj4v4gvoqdgqp.png)
![y\:=\:-(2)/(3)x\:\:+\:\left(-4\right)](https://img.qammunity.org/2022/formulas/mathematics/college/xnii567v7fxa4t5q2mr7i3fvoq7bwbo3xi.png)
![y\:=\:-(2)/(3)x\:-4](https://img.qammunity.org/2022/formulas/mathematics/college/qtky4vavmcuvw1rrepucvdb6woho9cf7pm.png)
We know that the equation in the standard form is
![Ax + By = C](https://img.qammunity.org/2022/formulas/mathematics/college/q5wz99lhcoxkn2kep0er34y35ime8u9bf1.png)
where x and y are variables and A, B and C are constants
so writing the equation in the standard form
![y\:=\:-(2)/(3)x\:-4](https://img.qammunity.org/2022/formulas/mathematics/college/qtky4vavmcuvw1rrepucvdb6woho9cf7pm.png)
![(2)/(3)x\:+\:y\:=-4](https://img.qammunity.org/2022/formulas/mathematics/college/hl68bc7lmmnqzc970548xfdjbac9c2y0x8.png)
Therefore, the equation in the standard form is:
![(2)/(3)x\:+\:y\:=-4](https://img.qammunity.org/2022/formulas/mathematics/college/hl68bc7lmmnqzc970548xfdjbac9c2y0x8.png)